Analysis of Attitudes and Approaches to Problem Solving: Gender Differences and Education Levels - Haeruddin Haeruddin; Kamaluddin Kamaluddin; Amiruddin Kade; Albar Rabak Pabianan (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
The main problem in this research is the low ability of students to solve physics problems. Students' attitudes and approaches to problem-solving are allegedly related to the way they study physics and their success in solving physics problems. This study demonstrated student attitudes and approaches to solving physics problems using Attitudes and Approaches to Problem Solving (AAPS) survey questions using quantitative methods. Data were collected from 1045 students. Data analysis was carried out by grouping the data by gender and education level. The t-test was used to see the differences in each group. The result showed no statistically significant differences between men and women (t = -1,65 dan Sig. = 0,098 > 0,05). In addition, there was a significant difference in the level of education between collect students with junior and senior high school education levels (p < 0.05). The implications for practice, and the directions for future research are discussed.